Approximation Theorems for Localized Baskakov Operators. (21st May 2021) - Xie, Linsen; Xie, Tingfan; Du, Hong
Abstract: We investigate the relation between the convergence of the localized Baskakov operators and the number of their terms N + 1. We obtain the limit functions and the approximation orders by the localized Baskakov operators under some conditions for N . A new estimate about the kernel of the Baskakov operators is achieved by using one of the central limit theorems in probability theory as well.